DELIVERY PROCESS OF GOODS AT PT. XYZ LOGISTICS - Husein Tuasikal (MANAGER: Journal of Management and Administration Science, 2022)
This study discusses the Process of Shipping Goods at PT. XYZ Logistics Bekasi. The research method uses the observation method and the library method. Based on the results of observations or observations made by researchers in the process of sending goods at PT. XYZ Logistics Bekasi, researchers found obstacles including a shortage of goods sent, damage to car engines so that shipments were delayed and customers were not served on time, and the solution that researchers proposed to overcome obstacles in the problem of shipping goods was that proper delivery vehicle facilities were needed. and adding operational vehicles for delivery of goods so that there are no delays in the delivery of goods, checking the engine before the truck carries out the process of loading goods so that the process of sending goods can run well, cooperation and accuracy are needed for warehouse employees in checking orders when loading goods so that there is no shortage or excess of goods which makes the outlet that ordered suffer losses because they have to re-order the goods.